A Case Study: Technological Pedagogical and Content Knowledge (TPACK) of Pre-service Physics Teacher to Enhance the 4C’s Skills During Online Learning - Yohanes Edi Gunanto; Lidya Anna Supriyadi (Postgraduate, University of Mataram, 2021)
Technological Pedagogical and Content Knowledge (TPACK) framework aims to provide an overview of teaching and learning that is integrated with technology to improve students' knowledge which supports 21st century skills. According to curriculum 2013 is expected to provide learning that develops students’ learning skills (critical thinking, creativity, collaboration, and communication) to face the world in the 21st century. The study is aimed to expose TPACK competence of pre-service teacher to enhance 10th grade students’ 21st century skills in physics learning. The method used descriptive qualitative, and data obtained from mentor’s feedback, teacher’s reflection in five meetings. As a result, TPACK component of pre-service teacher during five meetings of physics, was able to use technology to guide students well (TK1, TCK1, TPK1, and TPK2) and guide students to share ideas and knowledge (PK 3 and PCK3), discuss (PK4 and PCK4). The disadvantages of pre-service teachers which are still low is the content knowledge components and needs to be improved before becoming a professional teacher, so the teacher can integrate learning using technology properly. However, this study needs to be further developing the strategies to observed pre-service teacher